Led Işık Kaynaklı Armatür Isıl Modellenmesi Ve Isıl Tasarımı Etkileyen Faktörlerin İstatistiksel Analizi - Yurtseven, Mustafa Berker (Enerji Enstitüsü, 2017)
Tüketilen toplam elektrik enerjisi içinde yaklaşık %20 gibi önemli bir paya sahip aydınlatma tesisatlarında gerçekleştirilebilecek tasarruf önlemleri "enerji verimliliği" çalışmalarında üzerinde önemle durulan konular arasındadır. Bu kapsamda, az enerji harcayarak çok ışık üretebilen LED (light emitting diode - ışık yayan diyot) teknolojisi, etkinlik faktörlerinin (lm/W) yüksek olmasının yanı sıra, renksel geriverimlerinin iyileşmesi, farklı renk seçenekleri ve uzun ömürleri gibi özellikleri ön plana çıkarılarak, iç ve dış tesisatlarda genel aydınlatma amaçlı kullanılmaya başlanmıştır. Diğer yandan yarı iletken teknolojisinde yaşanılan hızlı gelişmeler sonucunda, LED'lerin etkinlik faktörleri sürekli artmaktadır. Ancak, açıklanan etkinlik faktörü değerleri, LED çiplerinin laboratuvar ortamlarındaki anlık çalışma koşulları için geçerlidir. LED'lerin ışık akıları ve ömürlerinin sıcaklık değişimlerinden, konvansiyonel ışık kaynaklarına oranla daha fazla etkilendiği bilinmektedir. Optimum çalışma sıcaklıkları aşıldığında, LED'lerin bozulma, devre dışı kalma oranları da yükselmekte, ışık akıları düşmekte ve renk özellikleri bozulmaktadır. Sonuç olarak, LED ışık kaynakları için açıklanan yüksek etkinlik faktörleri (lm/W) armatür formunda azalmaktadır. Piyasada bir çok LED ışık kaynağı kullanan aydınlatma armatürü bulunmaktadır. Bu armatürler hakkında üretici tarafından yeterli bilgi sağlanamaması, armatürlerin performanslarının yeterli olmaması ve bu konudaki standartların eksikliği nedeniyle, LED'lerin kullanıldığı aydınlatma tesisatları, konvansiyonel ışık kaynaklı olanlara göre iddia edildiği gibi üstün konuma gelememektedir. Fotometrik özelliklerinin belirlenmesinde de sorunlar olan LED'lerin, mevcut iç/dış aydınlatma tesisatlarında kullanılabilmeleri için, öncelikle armatür formunda aydınlatma standartlarında belirtilen aydınlık düzeyi, parıltı, düzgünlük ve kamaşma sınırlandırılması gibi minimum aydınlatma gereksinimlerini yerine getirmeleri gerekmektedir. Tüm aydınlatma armatürlerinde olduğu gibi LED'li armatürlerde de optik analizler, aydınlatma kalite kriterlerini sağlama bakımından tasarımın en önemli bölümüdür. Ancak, LED'li armatürlerde ışık kaynağının verimi sıcaklığa bağlı olduğu için, ısıl analizler de ön plana çıkmaktadır. Isıl analizler LED çipin monte edildiği baskı devre kartı (BD) ile çevresindeki soğutma elemanları ve armatür gövdesi olmak üzere iki aşamalıdır. LED tarafından üretilen ısının baskı devresi ile soğutma elemanlarından geçerek armatür gövdesi içine aktarımında ve gövde içindeki ısının da dış ortama geçişinde ısıl direncin minimum olması için, soğutucu aksamın tasarlanması gerekmektedir. Özellikle yüksek güçlü LED'lerin kullanıldığı armatürlerde verim, ısıl tasarım ile doğrudan ilişkilidir. LED armatür tasarımında ilk adım kullanılacak LED çipinin iyi analiz edilmesi olmalıdır. LED çiplerin optik-ısıl-elektriksel karakterizasyonu, tasarım aşamasından önce yapılmalı ve tasarım hedefleri buna göre belirlenmelidir. LED çipinin sıcaklığa bağlı olarak verdiği ışık miktarı, verimi, renk değişimi, optik ve ısıl güçlerinin ayrıştırılması ve çektiği gücün hesaplanması sıcaklık kontrollü ölçüm sistemleri yardımı ile belirlenmelidir. Özellikle LED çipin bilgisayar ortamında ısıl olarak simüle edilebilmesi için ısıl güç değerlerine ihtiyaç vardır. Bunun yanında armatürün etkinlik faktörünün belirlenmesi için de, LED çipin çalışacağı sıcaklıkta harcayacağı elektriksel gücün ve yayacağı ışık akısının bilinmesi gerekmektedir. LED çip karakterize edildikten sonra armatür tasarımı için kullanılacak malzemelerin termofiziksel özelliklerinin bilinmesi veya laboratuvar ortamında ölçülmesi gereklidir. Bir LED armatürü oluşturan LED çip, gövde (gövde malzemesi), baskı devre (BD) kartı, ısıl arabirim malzemesi gibi elemanların termofiziksel özelliklerinin biliniyor olması, simülasyon sonuçlarından uygulamaya geçişte daha doğru sonuçların alınmasını kolaylaştıracaktır. Sonuç olarak, LED'li armatürlerin aydınlatma için gerekli kriterleri sağlayacak optimum performansta çalışabilmeleri için, armatür tipine uygun optik analizlerin yapılması ve istenilen yeterli soğutma çözümlerine ulaşılması gerekmektedir. Bu tezde öncelikle LED ışık kaynaklarının özelliklerinin sıcaklık ile değişimi incelenmiş, armatür tasarım süreci hakkında bilgi verilmiş ve LED çiplerinin ısıl simülasyonlarında kullanılabilmesi için gerekli ısıl modellerin doğrulanması yapılarak bilgisayar destekli simülasyon süreci açıklanmıştır. Daha sonra LED armatür ısıl tasarımına etki eden gövde malzemesi ve yapısı, baskı devre kartı malzemeleri ve fiziksel özellikleri, ısıl arabirim elemanları, LED ısıl güçleri ve ortam sıcaklığı gibi faktörlerin etkilerinin anlaşılabilmesi için örnek bir yol aydınlatması armatürü üzerinde tam faktöriyel bir deney tasarımı yapılarak istatistiksel analiz gerçekleştirilmiş ve faktörlerin karşılıklı etkileşimleri incelenmiştir. Tez süresince yapılan simülasyon sayısının artması ve bir çok faktör seviyesi ile simülasyonların gerçekleştirilmesi sebebiyle, ikinci bir adım olarak, simülasyon sonuçlarına çok değişkenli doğrusal regresyon uygulanmış; faktör etkileri ve faktörlerin karşılıklı etkileri farklılık analizi (ANOVA – Analysis of Variance) ile istatistiksel olarak hesaplanmıştır. Bu yöntemle LED armatür ısıl tasarımına etki eden faktörlerin etkileri açıklanmış ve örnek bir LED armatür üzerinde ısıl simülasyonlar ve istatistiksel analizler gerçekleştirilerek özellikle LED armatür üreticilerine ve tasarımcılarına, LED armatür ısıl tasarım süreci hakkında yol gösterici bilgiler oluşturulması hedeflenmiştir.

Saving measures that can be realized in lighting installations with a significant share of about 20% in the total electricity consumed are among the issues emphasized in "energy efficiency" studies. In this context, LED (light emitting diode) technology, which can produce light by consuming less energy, has high efficacy factors (lm/W) and also has advantages such as high color rendering indexes, different color options, long life, started to be used for lighting purposes. On the other hand, the efficacy factors of LEDs are constantly increasing as a result of rapid developments in semiconductor technology. However, the announced efficacy factor values apply to the instantaneous operating conditions of the LED chips in the laboratory environment. It is known that the LED's light fluxes and lifetimes are much more affected by temperature variations than conventional light sources. When the optimum operating temperatures are exceeded, the LED's catastrophic failure ratios increase, the light intensity drops and the color characteristics deteriorate. As a result, the high efficacy factors (lm/W) announced for LED light sources are greatly reduced in the form of a luminaire. There are many luminaires in the market that use LED light sources. Due to the lack of technical information from the manufacturer, poor quality of the luminaires and and the lack of standards in this regard, the lighting installations in which the LEDs are used can not be in the superior position compared to conventional light sources as claimed. In order to be used in existing indoor/outdoor lighting installations; LEDs, which are still having problems in measurements of photometric quantities, are required to fulfill minimum lighting requirements such as illuminance, luminance, homogenity and glare limitation specified in lighting standards, in the form of a luminaire. The research on LEDs which are utilized in different areas continues for a long time. Most of the published work is about the LED's internal characteristics, production techniques and the use of different materials as semiconductors. As the LEDs gradually penetrate into lighting sector, the research focus shifted from prodction techniques to increasing performance, improving lighting characteristics, measuring thermal performance etc. Like in all lighting luminaires, optical analysis is the most important part of design for ensuring lighting quality criteria in LED luminaires. However, since the light source in LED luminaires is highly dependent on the temperature, thermal analyzes are also crucial. The thermal analyzes are carried out in two stages, the printed circuit board (PCB) on which the LED chip is mounted and the cooling elements and luminaire surroundings. In order to transfer heat in the luminaire through the cooling elements by the heat dissipated by the LED and to minimize the thermal resistance in the heat transfer inside the body, the cooling elements must be designed thoroughly. Especially for luminaires where high power LEDs are used, the efficiency is directly related to the thermal design. Depending on the type and power of the luminaire, thermal performance may greatly affect the overall luminaire performance. It is more difficult to transfer dissipated heat from the LED light sources for the luminaires with high Ingres Protection Class (IP) since the luminaires are water and dust proof whereas easier for the luminaires with low IP class. The first step in designing an LED luminaire should be a good analysis of the LED chip to be used. The optical-thermal-electrical characterizations of the LED chips must be done before the design phase and the design targets should be determined accordingly. The amount of light emitted by the LED chip depending on the temperature, the efficiency, the color change, the measurement and calculation of the optical, thermal powers and electrical power must be determined with the help of a temperature controlled measurement system. In particular, thermal power values are required for the LED chip to be thermally simulated in a computer environment. In order to determine the efficiency factor of the luminaire, it is necessary to know the electrical power and luminous flux of the LED chip for the working temperature. Usually the optical-thermal-electrical properties of the LED light sources are not given in the data sheets. Especially the luminous efficiency value is the essential part of the thermal simuation since the thermal power of the LED is calculated from this value. After characterizing the LED chip, the thermophysical properties of materials used for luminaire design must be known or measured in a laboratory environment. The accurate thermophysical properties of elements such as LED chip, body (body material), printed circuit board card (PCB) and thermal interface materials that make up an LED base luminaire will yield to get more accurate results in the transition from simulation results to application phase. The simulation software usually contains a library which the accurate thermophysical materials can be found. It is important to match the actual materials used to library materials accurately to reduce error. As a result, it is necessary to make optical analyzes according to the type of luminaire and optimize the required cooling solutions so that the luminaires with LED light sources can work with optimum performance to meet the necessary criteria for illumination. In the thesis, firstly the change of the properties of the LED light sources is investigated in the laboratory using a temperature controlled Ulbricht Sphere. For different temperatures the optical-mechanical-electrical characterization of the LEDs are shown. Then the luminaire design process is eloborated in detail and the computer aided simulation process is explained by verifying the thermal models required for the LED chips to be used in the thermal simulations. Two sample luminaires are chosen and then the compact thermal model used to characterize LED thermal models are validated using simulation results and laboratory measurements. Also photometric measurements are done and compared to predicted values using simulation results and catalog values. In order to investigate the effects of mechanical components, a statistical analysis is performed by designing a full factorial experiment on a sample road lighting luminaire prototype to understand the effects of factors such as body material, printed circuit board materials and physical properties, thermal interface elements, LED thermal power and ambient temperature and interactions between factors on a LED luminaire thermal design. A statistical software package is used to compare and calculate factor effects and interactions. After the preliminary analysis, simulations are carried out with many factor levels. Because of the increase in the number of simulations made during the research, as a second step, a multi variable linear regression model is applied to the simulation results. Factor effects and the interactions of these factors were statistically calculated by ANOVA (Analysis of Variance). Then using the multivariable regression model and the catalog values of the LEDs used in the luminaire, the photometric performance of the luminaire for different factor levels is investigated for different LED thermal power levels. Using a statistical regression model, the effects of the factors affecting the LED luminaire thermal design are explained and thermal simulations and statistical analyzes are performed on a sample LED luminaire, aiming to provide guidance about the LED luminaire thermal design process, especially to LED luminaire manufacturers and designers.
Thermal Modelling And Statistical İnvestigation Of Factors That Effects Thermal Design Of Led Light Source Based Luminaires
Tez (Doktora) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2017
Thesis (PhD) -- İstanbul Technical University, Institute of Science and Technology, 2017
Keywords: Sayısal akışkanlar dinamiği; Yapay aydınlatma; Yol aydınlatması; Computational fluids dynamic; Artificial lighting; Road lighting